The VHOT (Vindaloo Hastens Outpouring of Troponins) Study. (4th October 2016) - Tankel, Alan S; Nagree, Yusuf; Jones, Peter; Mountain, David; Macdonald, Stephen PJ; Hill, Paul; Than, Martin
Abstract: Background: Multiple cardiac and non‐cardiac processes may cause an elevated highly sensitive troponin (hsTn). We postulated that the consumption of a seriously hot vindaloo could cause an increase in hsTn levels in seemingly healthy volunteers. Objective: To determine whether eating a very hot curry can cause elevated hsTn. Methods: This was a prospective observational cohort study. Participants had blood drawn for hsTn pre‐ingestion and at 2 and 4 h post‐ingestion of, first, a rather mild butter chicken and, 2 weeks later, a seriously hot lamb vindaloo. We assessed pre‐curry tolerance and perception of curry hotness for both curries using the VHOT scale. Results: Although no participant had a troponin above the reference range at any point in time, we found dramatic relative increases in troponin in many of our participants. In the vindaloo phase, 8/22 (36%) had a relative change >20%, whereas 5/22 (23%) had a relative change >50% at 4 h. However, these changes were not significantly different to those in the butter chicken phase. Based on biological variability alone, 15/22 (68%) had a relative change of >20%, and 11/22 (50%) had a relative change of >50% between the two sessions (pre‐ingestion). Conclusions: Eating a seriously hot vindaloo does not appear to be a risk factor for troponitis, and people may consume vindaloo safely with the knowledge that this is unlikely to result in significant damage to their myocardium. However, clinicians should be aware of the biological variability of hsTn and exercise caution when interpreting apparent changes within the normal range.